Late ventricular potentials in familial Mediterranean fever with and without AA amyloidosis - Nussinovitch, Udi (Eur J Rheumatol, 2017)
OBJECTIVE: Familial Mediterranean fever (FMF) is an autosomal recessive disease characterized by episodic and chronic inflammation that may lead to both accelerated coronary atherosclerosis and cardiac AA amyloidosis. We hypothesized that late ventricular potentials (LPs), an established electrocardiographic susceptibility marker of ventricular arrhythmias, will be more common in FMF than in the adjusted normal population due to these two types of inflammation-associated cardiac effects. Therefore, we aimed to evaluate the occurrence of LPs in FMF patients with and without amyloidosis. MATERIAL AND METHODS: Signal-averaged electrocardiography was performed in consecutive patients with FMF using the Frank corrected orthogonal lead system. At least 200 consecutive beats were digitally recorded and averaged, and the presence of LPs was determined according to acceptable thresholds. RESULTS: There were 54 patients with colchicine-treated FMF, of whom 14 had biopsy-proven AA amyloidosis. None of the uncomplicated FMF patients and 2 of the 14 FMF amyloidosis patients had abnormal or borderline LPs. CONCLUSION: Based on LPs as a susceptibility marker for arrhythmia, FMF patients, including the large majority of FMF patients with amyloidosis, are seemingly not at an increased risk to develop arrhythmias.